2017
DOI: 10.18553/jmcp.2017.23.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Improving Comprehensive Medication Review Acceptance by Using a Standardized Recruitment Script: A Randomized Control Trial

Abstract: No outside funding supported this study. Research for this study was conducted while Liu was a postdoctoral fellow at the University of Florida. Liu is currently an employee of the U.S. Food and Drug Administration (FDA). The views expressed here are those of the authors and not necessarily those of the FDA. Yang reports receiving a research fellowship funded by WellCare Health Plans at the time of this study. The authors report no other potential conflicts of interest. Study concept and design were primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…Additionally, it is possible that personal relationships between community pharmacists and their patients resulted in more rapid patient acceptance of CMR offers. Recent literature has evaluated strategies, such as the use of scripted language, as well as phone calls and bag stuffers, for encouraging patients to accept CMR offers . As these practices become more common, research should examine whether changes in time from offer to CMR completion occur across provider types or are unique to specific provider types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it is possible that personal relationships between community pharmacists and their patients resulted in more rapid patient acceptance of CMR offers. Recent literature has evaluated strategies, such as the use of scripted language, as well as phone calls and bag stuffers, for encouraging patients to accept CMR offers . As these practices become more common, research should examine whether changes in time from offer to CMR completion occur across provider types or are unique to specific provider types.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has evaluated strategies, such as the use of scripted language, as well as phone calls and bag stuffers, for encouraging patients to accept CMR offers. 15,[34][35][36] As these practices become more common, research should examine whether changes in time from offer to CMR completion occur across provider types or are unique to specific provider types.…”
Section: Mtm Interventions Madementioning
confidence: 99%
“…87 Proactive communication training for pharmacy personnel, including the use of scripts, can generate demand for services and improve acceptance. 46,[88][89][90] Improving patient satisfaction and information about MTM services provided by pharmacies needs to become common so the services are sold through word-of-mouth. [91][92][93] There is a tremendous, untapped opportunity to improve patient expectations of community pharmacist-provided MTM services.…”
Section: Considerations To Improve Patient Engagement In Mtmmentioning
confidence: 99%
“…The last difference appeared in internal need between CMR recipients and nonrecipients were a couple patient characteristics: CMR recipients tended to use a higher number of prescriptions and had a poorer self-reported health status. These findings were consistent with previous studies that revealed older adults who took a higher number of medications and those having a poorer health status were more likely to demand or accept a CMR service (Brooks et al, 2008;Farris et al, 2016;Miguel et al, 2017). However, some patient characteristics that were expected to differentiate CMR recipient and nonrecipients base on literature, such as age (Brooks et al, 2008), gender (Brooks et al, 2008), and type of prescription coverage (Miguel et al, 2017;Perlroth et al, 2013), did not yield a statistically significant difference between CMR recipients and non-recipients.…”
Section: Differences In Internal Needsupporting
confidence: 91%
“…R. Carter et al, 2013). Our explanation also mirrored a recent randomized control trial where a recruitment script with emphasized benefits was found to engage more CMR participation than the script without highlighting benefits of CMRs (Miguel et al, 2017).…”
Section: )supporting
confidence: 68%